The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.5811/westjem.2017.1.32858
|View full text |Cite
|
Sign up to set email alerts
|

Audience Response System Facilitates Prediction of Scores on In-Training Examination

Abstract: IntroductionAudience response systems (ARS) are increasingly popular; however, their contribution to education is not completely clear. Our study found that scores from review quizzes delivered by an ARS correlate with in-training exam (ITE) scores and are viewed positively by residents. This information may be useful in identifying poor performers early so that targeted educational interventions can be made. The objective was to determine if scores on review quizzes delivered by an ARS correlate with ITE scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For them, it was easy and practical to use, engaged their participation, helped their understanding of the topic, and encouraged further discussion. This is consistent with a large body of research suggesting that residents and students respond positively to the use of ARS in medical education [ 7 , 16 ]. Our modification was to incorporate ARS in the context of This Week In SCORE and the associated multiple-choice questions (MCQ) component of the SCORE curriculum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For them, it was easy and practical to use, engaged their participation, helped their understanding of the topic, and encouraged further discussion. This is consistent with a large body of research suggesting that residents and students respond positively to the use of ARS in medical education [ 7 , 16 ]. Our modification was to incorporate ARS in the context of This Week In SCORE and the associated multiple-choice questions (MCQ) component of the SCORE curriculum.…”
Section: Discussionsupporting
confidence: 89%
“…An Audience Response System (ARS) is a technological tool that can encourage participation in a non-threatening manner, instantly collect learners’ responses, and display them in a way that is visually engaging and easy to comprehend [ 4 ]. ARS has been used in medical didactic sessions and morbidity and mortality conferences [ 5 - 7 ], with evidence that it improves knowledge acquisition and retention [ 8 ]. However, there are limited studies on the use of ARS to enhance interactive surgical education or its use in association with the Surgical Council on Residents Education (SCORE; www.surgicalcore.org ) curriculum for surgical residents and medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Shah et al demonstrated review quizzes delivered by ARS correlated with in-training exam scores in emergency medicine residents and was viewed positively [12]. Our study did not specifically evaluate whether ARS correlated with ACR In-Service exam scores, but rather tested whether those that received ARS performed better on the MSK section of the ACR In-Service exam score.…”
Section: Discussionmentioning
confidence: 93%
“…They have been shown to improve resident and attending satisfaction with smaller group didactics in radiology and emergency medicine as well as correlating to learning and retention in radiology, obstetrics, and family medicine; however, their utility in improving satisfaction with or selfperceived learning in IM or its subspecialties remains unclear [11][12][13][14][15]. Furthermore, the use of ARS for review quizzes has been shown to correlate to some residency specialty in-training exam scores, however, it remains unknown if the use of ARS would translate to improved IM board-subspecialty pass rates [16]. The Poll Everywhere® software specifically has not been evaluated in use in undergraduate or graduate medical education.…”
Section: Discussionmentioning
confidence: 99%